Urban Social Housing Pathways: A Linked Administrative Data Analysis. Issue 1 (2nd January 2021) - Baker, Emma; Pham, Anh; Leishman, Chris; Daniel, Lyrian; Bentley, Rebecca
ABSTRACT: This paper presents a national analysis of urban housing pathways. Focussing on the social housing sector, we follow social housing tenants as they move into, out of, and remain in, the sector over 15 years. Utilising a linked actuarial dataset, the paper reveals a typology of pathways, and examines the relationship between housing pathways and the receipt of broader government welfare. We find that not only is there no one social housing pathway in Australia; at different times in a household's housing career, social housing may be used by them as a momentary stepping-stone, a safety net, or a springboard.